USING ONLINE PEER REVIEW AS A STRATEGY TO IMPROVE WRITING SKILLS - Ula, Erfa Navadiatul; Umamah, Atik (IJIET (International Journal of Indonesian Education and Teaching), 2022)
This qualitative research was conducted to investigate the use of online peer review as a strategy to improve writing skills in the revision process. Two  English students of a private university in Malang were recruited based on two criteria: 1) they have passed an academic writing course with an excellent score, and 2) they use online media to conduct peer reviews. Using a semi-structured interview, the students were asked what types of online resources they use to perform online peer review, and how they do peer review online. The interview data were analyzed using content analysis. To triangulate the data, investigator triangulation was performed by involving two data analysts. The results of the study were that students mostly used WhatsApp and Zoom media to conduct online peer reviews. In addition, they used several platforms such as grammar checkers, online dictionaries to assist the revision process. The students shared their writing product in the form of a file to their peers via WhatsApp and improve the results of the feedback by utilizing online sources or obtaining reviews related to grammar, writing effectiveness, and diction errors.